IMPROVING PHYSICS LEARNING OUTCOMES WITH COOPERATIVE LEARNING NUMBERED HEAD TOGETHER TYPE ON OPTICAL DEVICES OF CLASS XI STUDENTS AT SMAN 1 SECANGGANG - Lubis, M.Surya Irawan; Derlina, Derlina ((IPER) Indonesian Physics Education Research, 2022)
This study aims to improve students' physics learning outcomes by applying NHT learning on optical instrument material. The population in this study were students of class XI of SMAN 1 Secanggang in the academic year 2023/2024. The samples in this study were XI MIPA 2 class as a control class totaling 30 students who were given conventional learning, and XI MIPA 3 class as an experimental class totaling 30 students who were given NHT learning. The sampling method used was quasi-experiment and used pretest-posttest control group design. Data on physics learning outcomes were collected using a test instrument in the form of 10 questions. The improvement of students' physics learning outcomes is seen by comparing the average value of hypothesis tests that are normally distributed and homogeneous in both classes. Based on the results of the study, it is concluded that the application of NHT learning on optical devices material can significantly improve student learning outcomes.